2013
DOI: 10.3945/jn.112.168021
|View full text |Cite
|
Sign up to set email alerts
|

Protein Blend Ingestion Following Resistance Exercise Promotes Human Muscle Protein Synthesis

Abstract: High-quality proteins such as soy, whey, and casein are all capable of promoting muscle protein synthesis postexercise by activating the mammalian target of rapamycin (mTORC1) signaling pathway. We hypothesized that a protein blend of soy and dairy proteins would capitalize on the unique properties of each individual protein and allow for optimal delivery of amino acids to prolong the fractional synthetic rate (FSR) following resistance exercise (RE). In this double-blind, randomized, clinical trial, 19 young … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
121
1
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(146 citation statements)
references
References 59 publications
9
121
1
6
Order By: Relevance
“…The observed slow rise in the rate of appearance of amino acids with the RPI is consistent with other non-meat, non-dairy proteins [20,21]. While research has indicated whey protein is fast absorbing and casein protein slower absorbing, when examined by change or rise in circulating amino acids values, the data also indicates protein in general, especially leucine-containing protein will stimulate MPS to occur.…”
Section: Resultssupporting
confidence: 52%
“…The observed slow rise in the rate of appearance of amino acids with the RPI is consistent with other non-meat, non-dairy proteins [20,21]. While research has indicated whey protein is fast absorbing and casein protein slower absorbing, when examined by change or rise in circulating amino acids values, the data also indicates protein in general, especially leucine-containing protein will stimulate MPS to occur.…”
Section: Resultssupporting
confidence: 52%
“…S6K and rpS6 compared with a whey protein beverage (Reidy et al, 2013). This signalling response closely matched changes in post-exercise rates of MPS, indicating a soydairy-based mixture of proteins can equally activate mTOR signalling and promote muscle growth responses to whey protein.…”
Section: Cellular Regulation Of Exercise Training Adaptation: a Primermentioning
confidence: 61%
“…A recent meta-analysis examining the efficacy of protein supplementation to increase lean body mass and strength after REX training revealed that protein supplementation significantly increased muscle mass and strength compared with placebo (Cermak et al, 2012). While the anabolic capacity of protein availability in human skeletal muscle is primarily attributable to the ingestion of essential amino acids (EAAs) and in particular the branched chain amino acid leucine, factors such as the dose (Moore et al, 2009a;Witard et al, 2013), source (Reidy et al, 2013;Tang et al, 2009;Tipton et al, 2004) and the timing/distribution of intake (Areta et al, 2013;Esmarck et al, 2001) also modulate the effectiveness for protein supplementation to augment muscle mass with REX. The 'anabolic' signalling pathways activated by REX and protein ingestion centre on intramuscular mTORC1 signalling (Kimball and Jefferson, 2010).…”
Section: Cellular Regulation Of Exercise Training Adaptation: a Primermentioning
confidence: 99%
“…Además, Reidy y Cols. 60 añaden que con un suplemento de mezcla de proteí-nas la respuesta anabólica de esta quinasa se prolonga en el tiempo posingesta en comparación a la misma ingesta de proteína de suero de leche. Por lo tanto, según estos tres estudios, la presencia de leucina adquiere un rol relevante para la activación de la ribosomal s6 quinasa.…”
Section: Motivo De Exclusiónunclassified
“…46 indican que estas quinasas aumentan después del ejercicio pero con independencia a una suplementación y sin diferencias entre BCAAs más HC o HC solos. En cambio, otros estudios 60,62,63 muestran cómo la fosforilación de la Akt aumenta después del ejercicio y la ingesta de diferentes protocolos de suplementación con proteínas y BCAAs. Por lo tanto, con estas referencias actuales, se hace difícil especular, intuir y teorizar con dosis eficaces y seguras, posologías y tipo de proteínas y/o AAEs/BCAAs para activar óptimamente estas dos quinasas.…”
Section: Motivo De Exclusiónunclassified